2021
DOI: 10.51821/84.3.012
|View full text |Cite
|
Sign up to set email alerts
|

The role of neuromodulation in chronic functional constipation : a systematic review

Abstract: Background : Chronic functional constipation is a highly prevalent disorder in which, when conservative measures fail to relieve symptoms, surgical interventions are sometimes indicated. In recent years, neuromodulation for the treatment of functional constipation has gained interest but its role and effectiveness are still unclear. The purpose of this review is to provide a systematic overview on the current literature on the different modalities of neurostimulation and their effect on chronic functional cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 60 publications
1
5
0
3
Order By: Relevance
“…No side effects occurred in any patient in both therapeutic groups. This was similar to the literature in which BF and PTNS were considered safe physical modalities and not associated with any side effects [ 13 , 15 , 16 , 30 , 31 , 36 38 , 54 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…No side effects occurred in any patient in both therapeutic groups. This was similar to the literature in which BF and PTNS were considered safe physical modalities and not associated with any side effects [ 13 , 15 , 16 , 30 , 31 , 36 38 , 54 ].…”
Section: Discussionsupporting
confidence: 89%
“…During the neuromodulation session, the patient is completely passive. No need for any active participation of the patient during the session [ 53 , 54 ]. The effect of neuromodulation takes place in a subconscious level that the patient could not recognize it except by the observation that the OD is gradually improved [ 15 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Weniger eindeutig ist die Bedeutung der SNM in der Therapie der Obstipation. Da Patienten, die aufgrund urologischer Erkrankungen behandelt wurden, eine Verbesserung der Darmmotilität unter Neuromodulation beobachteten, wurde das Konzept auch bei den verschiedenen Formen der Obstipation (Normal Transit, Slow Transit oder Auslassobstruktion) angewendet [8,45]. Obwohl viele Untersuchungen nur wenige Patienten einschließen und häufig nicht klar zwischen den verschiedenen Untergruppen der Obstipation unterschieden wird, lässt sich absehen, dass die Neuromodulation hier bei vergleichbarem Komplikationsprofil wie in der Behandlung der Stuhlinkontinenz [46] zu weit geringerer Beschwerdebesserung führt als bei dieser (▶ Tab.…”
Section: Sakrale Neuromodulation Bei Obstipationunclassified
“…Insbesondere konnten 2 doppelblinde, randomisierte Cross-over-Studien keine Wirkung der SNM belegen [47,48]. Allerdings lässt die Zusammenschau der bisherigen Studien vermuten, dass das in die verschiedenen Studien jeweils eingeschlossene Patientenkollektiv sehr inhomogen ist und möglicherweise bei Subgruppen der Patienten ein therapeutischer Effekt erzielt werden kann [45,49]. Da aufgrund der eingeschränkten Datenlage therapeutischer Benefit bei einzelnen Subgruppen der Obstipation bestehen kann und mit der Probestimulation ein kaum invasives Testverfahren zur Verfügung steht, kann nach Ausschöpfung der konservativen Behandlungsmöglichkeiten nach derzeitigem Kenntnisstand ein Therapieversuch mit der SNM in Betracht gezogen werden, insbesondere vor dem Hintergrund, dass chirurgische Alternativen sehr viel invasiver und z. T. irreversibel sind, wie z.…”
Section: Sakrale Neuromodulation Bei Obstipationunclassified
“…SNS has proven to be a reliable method for dealing with FI in children[ 112 ]. Clinical trials have also shown that SNS can help with FI[ 113 ]. Another extensive approach conveys the benefits of SNS in patients with neuropathic FI[ 114 ].…”
Section: Sacral Neuromodulation In Fecal Incontinencymentioning
confidence: 99%